Transition to adulthood during military service : the Israeli case - Lieblich, Amia, 1939- (Albany : State University of New York Press, 1989)
Annotation A developmental study of men in mandatory military service based on interviews of young soldiers who had recently completed their service in Israel. The book deals with the central issues of transition to adulthood and the psychological effects of military service in the context of the previous research and theory concerning these subjects. Paper edition (unseen), $14.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Part 1: Personal accounts -- Part 2: Routes and issues of psychological development.
Includes bibliographical references (pages 197-211) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Draft -- Israel -- Psychological aspects -- Case studies; Teenage boys -- Israel -- Case studies; Men -- Israel -- Psychology -- Case studies; Soldiers -- Israel -- Psychology -- Case studies; Psychology, Military -- Case studies; Service militaire obligatoire -- Israël -- Aspect psychologique -- Études de cas; Garçons adolescents -- Israël -- Études de cas; Hommes -- Israël -- Psychologie -- Études de cas; Psychologie militaire -- Études de cas; TECHNOLOGY & ENGINEERING -- Military Science; HISTORY -- Military -- Other; Draft -- Psychological aspects; Men -- Psychology; Psychology, Military; Soldiers -- Psychology; Teenage boys; Israel; Jugendsoziologie; Militärausbildung; Wehrdienst; Israel; Militaire dienst; Volwassenwording; Psychologische aspecten; Case studies; Erlebnisbericht